1999
DOI: 10.1002/(sici)1097-4547(19990615)56:6<611::aid-jnr7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Structural and compositional determinants of cortistatin activity

Abstract: Cortistatin-14 (CST-14) is a putative novel neuropeptide that shares 11 of its 14 residues with somatostatin-14 (SRIF-14), yet its effects on sleep physiology, locomotor behavior and hippocampal function are different from those of somatostatin. We studied the structural basis for cortistatin's distinct biological activities. As with SRIF-14, CST-14 does not show any preferred conformation in solution, as determined by circular dichroism and nuclear magnetic resonance. Synthetic cortistatin analogs were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Structure-activity relationship studies on the cortistatin peptide show that the extracyclic N-terminal proline and the C-terminal lysine amide are essential for its distinct biological properties (19). This suggests that both of these residues are required for binding of cortistatin to its specific receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-activity relationship studies on the cortistatin peptide show that the extracyclic N-terminal proline and the C-terminal lysine amide are essential for its distinct biological properties (19). This suggests that both of these residues are required for binding of cortistatin to its specific receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-activity relationship studies have indicated that the Pro moiety at position 2 and the C-terminal Lys residue are crucial for the distinctive effects of CST in the brain (Criado et al 1999). Based on these data, the existence of specific CST receptors able to bind selectively to CST but not to SS1 has been postulated.…”
Section: Uts2r5mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 9 As indicated above, previous studies show that CST has a high affinity for the different human sst subtypes in stably transfected cell lines (Criado et al, 1999). The expression of two other known receptors capable of binding CST, MrgX2 and GHS-R, in the immune system is a less explored field.…”
Section: Page 9 Of 20mentioning
confidence: 99%
“…The SRIF receptor genes are all located on different chromosomes, but have a high degree of sequence homology (Patel et al, 1996). CST binds with high affinity to all 5 sst subtypes (Criado et al, 1999;Fukusumi et al, 1997;Siehler et al, 1998). The function of SRIF has been studied far more in depth: it can act as a neurotransmitter and neurohormone and in peripheral tissues it regulates endocrine and exocrine secretion and acts as a modulator of motor activity in the gastrointestinal tract (Reichlin, 1983a;Reichlin, 1983b).…”
Section: Introductionmentioning
confidence: 99%